The Shortening of Sustainable Supply Chains in Hungary and Europe - Szabó, Zoltán Tamás; Chuluunbaatar, Erdenebayar; Alpek, B. Levente (Journal of Central European Green Innovation, 2023)
The study examines the impact of supply disruptions arising from the COVID-19 pandemic and the energy security challenges primarily resulting from the Russian-Ukrainian war on the re-evaluation of sustainability considerations and the European green transition, especially regarding the potential strategic importance of renewable energy sources. The justification for the shortening of the long supply chains can be argued from the perspectives of supply security and sustainability. Furthermore, the economic validation of sustainability considerations is receiving increasing attention in professional discourse, sparking public debate. One of the primary tensions underlying these polemics is the conflict between short-term economic interests and long-term sustainability and environmental considerations. These interests often contradict each other, and the ongoing professional debate surrounding the shortening of supply chains provides relevant insight into these conflicts. However, the supply disruptions resulting from COVID-19 have re-emphasized the importance of supply security, prompting many economic actors to reconsider their supply strategies. The growing significance of supply security is evident in surveys, expert analyses, and economic strategic documents. The energy challenges posed by the Russian-Ukrainian war have, in turn, prompted EU policymakers to reform the energy strategy. The risks associated with energy security highlighted the vulnerabilities stemming from dependency on external fossil-based energy sources. This article aims to answer the question of how short-term economic interests and longer-term sustainability goals can be reconciled in light of the supply disruptions experienced during COVID-19 and the Russian-Ukrainian war. It does this through a literature review of professional debates and relevant expert analyses, strategic EU documents, and by examining key indicators of the EU’s energy dependence. The restructuring of the EU’s energy policy demonstrates the feasibility of rapidly implementing major transformations in complex systems when necessary. Beyond facilitating professional discourse, the experiences from these events can also boost the European green transition, as a green Europe built on its renewable resources can be more resilient against challenges of the future. This is in line with both economic and environmental objectives. The main conclusion of the research is that the EU’s successful transition to renewable energy sources, in addition to achieving environmental goals, can contribute to reducing external risks through the alleviation of energy dependence. Furthermore, energy security provided by its own energy sources facilitates the growth of the real economy and underpins the EU’s geopolitical position.